Pronounced cortisol response to acute psychosocial stress in type 2 diabetes patients with and without complications - Buckert, Magdalena; Hartmann, Mechthild; Monzer, Nelly Lou; Wolff, Kira; Nawroth, Peter Paul; Fleming, Thomas; Streibel, Carmen; Henningsen, Nikola; Wild, Beate (Hormones and behavior, 2022)
It is increasingly recognized that psychological stress is linked with type 2 diabetes mellitus and its late complications. Thus, the aim of the current study was to investigate the psychophysiological response to acute psychosocial stress in patients with type 2 diabetes. In total, 53 type 2 diabetes patients with complications, 16 type 2 diabetes patients without complications, and 47 age and gender matched non-diabetic participants underwent the Trier Social Stress Test. Subjective as well as biological parameters (i.e., blood levels of cortisol, adrenocorticotropic hormone (ACTH), norepinephrine, methylglyoxal) were assessed repeatedly before and after stress induction. Data were analyzed by means of multilevel regression. Patients with type 2 diabetes showed an exaggerated cortisol response to acute stress as compared to age matched control participants (diabetes*T2 est. = 1.23, p < .001), while stress-induced alterations of ACTH and subjective parameters did not differ. Norepinephrine levels were lower among patients (diabetes est. = −4.36, p = .044) and tended to decrease earlier than in controls. The subjective reaction of type 2 diabetes patients with complications was stronger than that of patients without complications (complication*T2 est. = −1.83, p = .032), while their endocrine response to stress was similar. Stress had no effect on methylglyoxal level, and there were no group differences regarding methylglyoxal response. These results show that the cortisol reactivity of patients with type 2 diabetes to acute psychosocial stress is increased compared to a control group. Thus, alterations of the hypothalamus-pituitary-adrenal axis - especially regarding its dynamic regulation - are a plausible link between psychological stress and type 2 diabetes and its complications.